2017
DOI: 10.1080/09593330.2017.1370020
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of sewage sludge-biomass gasification residue in cement-based materials: effect of pozzolant type

Abstract: In this study, the viability to utilize the residue, obtained from a sewage sludge (SS) and biomass combustion/gasification plant (GR), in cement-based materials was analysed. Two pozzolanic materials were selected to make GR more recyclable: metakaolin (MK) and spent catalyst waste (Z), received from fluidized-bed catalytic cracking process. Functional and environmental properties of standard cement pastes and mortars as well as binary and ternary combinations of GR with MK and Z were assessed. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Special attention has been paid to the characterization of bottom ashes from SS gasification, which is of particular interest for their safe management or further valorization in the context of circular economy. In fact, depending on the specific chemical-physical properties, ashes from SS thermal treatment could be conveniently employed either in the development of materials for building application , or as adsorbent materials, i.e., for hot H 2 S removal, or further treated for P recovery, and so on, rather than disposed of in landfills. However, while the properties of ashes arising from SS incineration have been extensively studied so far, to the best of the authors’ knowledge, only a few studies are available in the literature relative to the in-depth characterization and further valorization of SS gasification ashes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Special attention has been paid to the characterization of bottom ashes from SS gasification, which is of particular interest for their safe management or further valorization in the context of circular economy. In fact, depending on the specific chemical-physical properties, ashes from SS thermal treatment could be conveniently employed either in the development of materials for building application , or as adsorbent materials, i.e., for hot H 2 S removal, or further treated for P recovery, and so on, rather than disposed of in landfills. However, while the properties of ashes arising from SS incineration have been extensively studied so far, to the best of the authors’ knowledge, only a few studies are available in the literature relative to the in-depth characterization and further valorization of SS gasification ashes.…”
Section: Resultsmentioning
confidence: 99%
“…To implement the circular economy targets, particular attention is paid to the sludge-to-energy (StE) technologies, which allow not only the waste volume to be reduced, but also direct energy or fuels (as energetic vectors) to be generated, , natural resources (e.g., land) to be saved, and valuable byproducts (e.g., SS ash, biochar, digestate) to be obtained for use as raw materials or marketable products, including adsorbent materials, , unconventional source of phosphorus, construction and building materials. Among the currently available StE technologies, the ones involving the thermochemical treatment of sludge, such as combustion (for the direct production of energy), pyrolysis (together with oxy-pyrolysis and torrefaction), and gasification (the last two for the production of a fluid with energetic value), appear particularly promising because of the very good performances in terms of short reaction times (from seconds to minutes) and high conversion efficiency (less than 20% of unconverted organic constituents at the end of the process) also in comparison to the biochemical conversion routes such as anaerobic digestion (reaction time from 7 days to 5 weeks; about 40–70% of unconverted organic constituents) …”
Section: Introductionmentioning
confidence: 99%
“…Metakaolin (MK) was selected as the source of aluminosilicate material, obtained after calcination of kaolin clay at 800 • C for 2 h. Kaolin clay's and MK's chemical composition and particle size are presented in detail elsewhere [34,35]. The activation solution was a sodium silicate solution (JSC Rameta, Vilnius, Lithuania), with a SiO 2 /Na 2 O ratio of 3.3 and a density of 1.25 g/cm 3 .…”
Section: Geopolymer Materialsmentioning
confidence: 99%
“…After adding the binder, the solidified waste can undergo a series of physicochemical reactions, which can stabilize the incorporated toxic substances and improve the mechanical property of SS simultaneously [12][13][14][15][16] . Then the physical and chemical properties of the SSS meet the requirements for disposal in a landfill or use in engineering applications, such as for bricks, subgrade and landfill cover 11,[17][18][19][20][21] . Lim 15 reported that the unconfined strength of the solidified sludge by fly ash and loess satisfied the criteria for construction materials, which was above 100 kPa.…”
Section: Strength and Microstructure Properties Of Solidified Sewage mentioning
confidence: 99%